BACK SCHOOL AS AN OPTION TO PREVENT POOR BODY POSTURE OF 11 – 14 YEARS OLD CHILDREN (Fiep Bulletin - online, 2014)
Postural function to some extend reflects the overall health of the child and is one of the major factors involved in the quality of health. High incidence of functional disorders of the musculoskeletal system in children of school age reflects changes to current lifestyle of modern population, characterized by a significant decrease in the volume and intensity of physical activity, increased static activity in improper working positions. The quality of postural functions in childhood is considered to be a sensitive indicator of external stress factor, accompanying the vast majority of school-age children. The objective of the research was to evaluate body posture of 11 to 12 year olds at one of the Bratislava’s primary schools. In collaboration with physiotherapists, we focused our attention on the detection of posture with scoliosis, poor posture and incidence of flat feet. The body posture was evaluated according to visual aspects and the foot scanner was used to examine their feet. After evaluating postural functions of children the parents and teachers were informed on the results of the measurements. Another part of the project was illustrative presentation of the back school and ergonomic seating directly in the classroom.
Keywords: body posture; postural function; functional disorders of the musculoskeletal system; back school; ergonomic seating